2007
DOI: 10.1002/eji.200737097
|View full text |Cite
|
Sign up to set email alerts
|

EphrinB1‐EphB signaling regulates thymocyte‐epithelium interactions involved in functional T cell development

Abstract: The Eph and ephrin families are involved in numerous developmental processes. Recently, an increasing body of evidence has related these families with some aspects of T cell development. In the present study, we show that the addition of either EphB2-Fc or ephrinB1-Fc fusion proteins to fetal thymus organ cultures established from 17-dayold fetal mice decreases the numbers of both double-positive (CD4 + CD8 + ) and singlepositive (both CD4 + CD8 -and CD4 -CD8 + ) thymocytes, in correlation with increased apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 47 publications
8
68
0
1
Order By: Relevance
“…However, several data support a direct role of both ephrin-B1 and -B2 expressed by TECs on T cell development. Both ephrin-Bs are expressed by mature TECs (12), and published results reveal that EphB2 and/ or EphB3 forward signaling on thymocytes that depend on signals provided by TECs modulate DP T-TEC adhesion, T cell development, and TCR stimulation (14,45). Therefore, our current results on the effects of TEC-conditioned mutations on adult T cell development can be interpreted as the sum of a direct role plus the indirect consequence of an altered TEC maturation.…”
Section: Discussionsupporting
confidence: 54%
“…However, several data support a direct role of both ephrin-B1 and -B2 expressed by TECs on T cell development. Both ephrin-Bs are expressed by mature TECs (12), and published results reveal that EphB2 and/ or EphB3 forward signaling on thymocytes that depend on signals provided by TECs modulate DP T-TEC adhesion, T cell development, and TCR stimulation (14,45). Therefore, our current results on the effects of TEC-conditioned mutations on adult T cell development can be interpreted as the sum of a direct role plus the indirect consequence of an altered TEC maturation.…”
Section: Discussionsupporting
confidence: 54%
“…Recently, Hansen et al elegantly demonstrated that ephrin-As induced the biphasic retinal axon growth [21]. Alfaro et al [7] demonstrated that immobilized Eph-B2-Fc and ephrin-B1-Fc modulated the anti-CD3 antibody-induced apoptosis of CD4 + CD8…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, there are nine EphAs that bind to five ephrin-As, and five EphBs (B1, B2, B3, B4, B6) that bind to three ephrin-Bs (B1, B2, B3 [2,5,6], their physiological role in immune responses are still not known. Studies have shown that a deficiency of certain Ephs leads to a defect in thymocyte maturation because of abnormal development of the stromal cells [7][8][9][10]. The effects of Eph receptors expressed on mature T cells have been reported, such as modulation of chemotaxis by certain ephrin-As and ephrin-Bs [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…81 In addition, it has been shown that some chemorepellent molecules, including semaphorins and ephrins, affect thymocyte differentiation during their development. [82][83][84] Sema3E, which interacts with plexin-D1 in an NP-1-independent manner, was recently reported to participate in thymocyte development. 82 Plexin-D1 expression is high in CD4 1 CD8 1 thymocytes (double-positive, DP) but decreased in single-positive cells.…”
Section: Semaphorins In the Thymusmentioning
confidence: 99%